Electrochemical Sensors Based on Single-Wall Carbon Nanotubes in Voltammetric Ascorbic Acid Tests - Natalia V. Ivanova; Elizaveta A. Martynova; Anna I. Vershinina; Maksim V. Lomakin; Galina O. Eremeeva; Olesya R. Gordaya; Sergey D. Shandakov (Техника и технология пищевых производств)
Modern highly sensitive and selective sensors are able to determine biologically active substances, which makes this direction one of the most popular areas of analytical chemistry. The study featured the electrochemical properties of new fiber materials based on single-wall carbon nanotubes with prospects of using them in the voltammetry of ascorbic acid. The authors developed a new technology to synthesize films from disordered single-wall carbon nanotubes by chemical vapor deposition. Fibers were produced from a solvent by wet-pulling of single-wall carbon nanotubes networks. Thin films of randomly oriented single-wall carbon nanotube bundles were deposited downstream of a floating aerosol CVD reactor, which included a high temperature furnace with a quartz tube. The synthesis of the single-wall carbon nanotube samples was performed at 825°C. Ethanol served as carbon source while ferrocene was used as catalyst precursor. The single-wall carbon nanotubes were collected on a nitrocellulose filter in the form of films with transmittances of 10% in the middle of the visible wavelength (550 nm). The method was optimized to involve air annealing at 300–320°C and a treatment with strong inorganic acids, i.e., HCl, HNO3 + H2 SO4 . The voltammetric curves recording included background electrolyte, scan rate, and preconditioning. These parameters were selected experimentally to obtain the maximal sensor response to ascorbic acid content. The anodic peak of ascorbic acid in the phosphate buffer electrolyte (pH 6.86) was observed at a potential of +0.2 V. The current and peak area of ascorbic acid oxidation depended neither on the time nor on the conditioning potential of the sensor. The linear dependences of these parameters on the concentration of ascorbic acid stayed within 50–500 μmol/L (8.8–90 mg/L) at а scan rate of 0.1 mV/s. The single-wall carbon nanotube microsensor had a length of 0.5 cm and an average width of 400 μm. Its sensitivity was two times as high as that of a disk glassy carbon electrode with a diameter of 5 mm. The experimental sensors proved effective in determining ascorbic acid in food products, pharmaceuticals, and biological fluids.